Cover Image. Issue 1 (February 2017) - Tolbert, Allison; Ragauskas, Arthur J.
Abstract : The cover image, by Allison Tolbert and Arthur J. Ragauskas, is based on the Review Advances in understanding the surface chemistry of lignocellulosic biomass via time‐of‐flight secondary ion mass spectrometry, DOI:10.1002/ese3.144 . The authors would like to acknowledge the following image contributors: Robert Davies (Renewable Bioproducts Institute, Georgia Tech) greatly assisted with the image formatting, Wellington Muchero and Jay Chen (Oak Ridge National Laboratory) and Bruce Arey (Environmental Molecular Science Laboratory) provided the Helium Ion Microscope image of Populus cell walls, and Chang Geun Yoo (Oak Ridge National Laboratory) assisted with the creative design.